Actividades físicas para desarrollar las habilidades motrices básicas en niños de 5to curso de la Escuela Federico Gonzales Suarez - Romero Jurado, Mary Belen (2023)
The process of developing basic motor skills (walking, running, jumping, throwing and catching). Physical exercise is aimed at responding to movement problems that arise for the student at school, such as basic motor skills. This research was developed to benefit 8-year-old students with the objective of designing a physical activity plan to develop basic motor skills in 5th grade children at the Federico Gonzales Suarez school. To support this research, information was collected through interviews, surveys and the observation guide, which provided us with important data that highlight the importance of applying physical exercises aimed at the institution's students.